2006
DOI: 10.1097/01.mjt.0000212705.79248.74
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Type A in Prophylactic Treatment of Migraine

Abstract: Current migraine preventive therapies are often unsatisfactory because of their limited efficacy, adverse effects, and drug interactions. An open-label, non-controlled study of botulinum toxin type A (BTX-A) suggested some benefits for patients with migraine. To assess the efficacy and safety of BTX-A, a randomized, double-blind, vehicle-controlled, parallel group study was conducted in 32 patients with a history of 2 to 8 migraine attacks per month, with or without aura. The patients were randomized to receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Botulinum toxin type A (BoNT-A) has been recently proposed as a new option in this approach. At present, this drug plays a possible role in the treatment of both chronic forms of TTH and migraine [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Botulinum toxin type A (BoNT-A) has been recently proposed as a new option in this approach. At present, this drug plays a possible role in the treatment of both chronic forms of TTH and migraine [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…12 papers were unretrievable. A total of 184 retrievable papers, containing reports on 145 acute [17148] and 52 prophylactic trials [149198], were considered eligible for further review.…”
Section: Resultsmentioning
confidence: 99%
“…We chose 50‐U BTX‐A because of its cost‐effectiveness and to reduce the incidence of adverse events such as weakness, neck pain, blepharoptosis and cost. Research has shown pericranial injection of 50‐U BTX‐A to be efficacious and well‐tolerated as a prophylactic agent [25] and various studies have had similar results for BoNT‐A as a stand‐alone prophylaxis agent for headache in patients with a history of migraine or probable migraine headache [26] . However, in other studies, the efficacy of BoNT‐A in preventing migraine headache attacks remains controversial.…”
Section: Discussionmentioning
confidence: 99%